Effect of Multiple Medicines on Dementia Initial Treatment: Experience and Thinking. (26th November 2021) - Gan, Jinghuan; Wang, Meng; Liu, Shuai; Chen, Zhichao; Wang, Xiao-Dan; Ji, Yong
Little is known about multiple medicines and initial therapy among people with dementia. To examine the effect of multiple medicines on the initiation of anti-dementia therapy in patients diagnosed with cognitive impairment (CI), a retrospective study with 2742 CI patients was conducted based on the outpatients' medical records. The dementias receiving 1–2 drugs were more likely to be prescribed with anti-dementia (one drug: OR = 1.877; two drugs: OR = 1.770) and psychotropic (one drug: OR = 1.980) treatment, whereas had lower chances of receiving psychotropic medication with the combinations of more than three drugs (Alzheimer's disease: OR = .365; vascular dementia: OR = .940; frontotemporal lobe degeneration: OR = .957; and dementia with Lewy bodies/Parkinson's disease dementia: OR = .952). Multiple medicines can affect anti-dementia therapy initiation in dementia patients and should be paid extreme caution.